Predicting the suitability of aqueous solutions of deep eutectic solvents for preparation of co-continuous porous carbons via spinodal decomposition processes - Posada, E.; Lopez Salas, Nieves; Carriazo, D.; Muñoz-Márquez, M.A.; Ania, C.O.; Jiménez-Riobóo, R.J.; Gutiérrez, M.C.; Ferrer, M.L.; Monte, F. del (Carbon)
Keywords: General Chemistry; General Materials Science

Silica Polymerization from Supersaturated Dilute Aqueous Solutions in the Presence of Alkaline Earth Salts - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Insight into the Final Step of the Supramolecular Buildup of Eumelanin - Büngeler, Anne; Hämisch, Benjamin; Huber, Klaus; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Threshold Switching Induced by Controllable Fragmentation in Silver Nanowire Networks - Wan, Tao; Pan, Ying; Du, Haiwei; Qu, Bo; Yi, Jiabao; Chu, Dewei (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko (Materials & Design)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Liquid crystals and precious metal: from nanoparticle dispersions to functional plasmonic nanostructures - Atorf, Bernhard; Funck, Timon; Hegmann, Torsten; Kempter, Susanne; Liedl, Tim; Martens, Kevin; Mühlenbernd, Holger; Zentgraf, Thomas; Zhang, Bingru; Kitzerow, Heinz-Siegfried; Urbanski, Martin (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Pollution Control Meets Sustainability: Structure-Activity Studies on New Iron Oxide-Based CO Oxidation Catalysts - Schoch, Roland; Bauer, Matthias (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Insight into Fast Nucleation and Growth of Zeolitic Imidazolate Framework-71 by In Situ Time-Resolved Light and X-ray Scattering Experiments - Saha, Sanjib; Springer, Sergej; Schweinefuß, Maria E.; Pontoni, Diego; Wiebcke, Michael; Huber, Klaus (Crystal Growth & Design)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Inverter Circuits Using ZnO Nanoparticle Based Thin-Film Transistors for Flexible Electronic Applications - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Nanomaterials)
Keywords: General Materials Science; General Chemical Engineering

Hot isostatic pressing of IN718 components manufactured by selective laser melting - Tillmann, Wolfgang; Schaak, Christoph; Nellesen, J.; Schaper, Mirko; Aydinöz, Mehmet Esat; Hoyer, Kay-Peter (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

Gelled Lyotropic Liquid Crystals - Xu, Yang; Laupheimer, Michaela; Preisig, Natalie; Sottmann, Thomas; Schmidt, Claudia; Stubenrauch, Cosima (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Chemically and thermally stable, emissive carbon dots as viable alternatives to semiconductor quantum dots for emissive nematic liquid crystal–nanoparticle mixtures with lower threshold voltage - Urbanski, Martin; Mirzaei, Javad; Sharma, Anshul; Hofmann, Daniel; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Phosphorus-doped carbon–carbon nanotube hierarchical monoliths as true three-dimensional electrodes in supercapacitor cells - Patiño, Julián; Lopez Salas, Nieves; Gutiérrez, María C.; Carriazo, Daniel; Ferrer, M. Luisa; Monte, Francisco del (Journal of Materials Chemistry A)
Phosphorus-doped carbon–carbon nanotube hierarchical monoliths exhibiting energy densities of around 22.6 W h kg−1 at power densities of up to 10 kW kg−1 were capable of functioning as true three-dimensional electrodes in supercapacitor cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Nitrogen-doped carbons prepared from eutectic mixtures as metal-free oxygen reduction catalysts - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Muñoz-Márquez, Miguel A.; Luisa Ferrer, M.; Monte, Francisco del (Journal of Materials Chemistry A)
Deep eutectic solvents (DESs) composed of resorcinol, either 2-cyanophenol or 4-cyanophenol, and choline chloride were used for the synthesis of hierarchical nitrogen-doped carbon molecular sieves.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Efficient nitrogen-doping and structural control of hierarchical carbons using unconventional precursors in the form of deep eutectic solvents - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Fierro, José Luís G.; Luisa Ferrer, M.; Monte, Francisco del (J. Mater. Chem. A)
Deep eutectic solvents formed with unconventional carbon precursors were used for the preparation of hierarchical carbon monoliths and proved effective for doping the resulting carbons with nitrogen.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Use of Eutectic Mixtures for Preparation of Monolithic Carbons with CO2-Adsorption and Gas-Separation Capabilities - Lopez Salas, Nieves; Jardim, E. O.; Silvestre-Albero, A.; Gutiérrez, M. C.; Ferrer, M. L.; Rodríguez-Reinoso, F.; Silvestre-Albero, J.; del Monte, F. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Sulfur-Doped Carbons Prepared from Eutectic Mixtures Containing Hydroxymethylthiophene as Metal-Free Oxygen Reduction Catalysts - Lopez Salas, Nieves; del Monte, Francisco; Tamayo, Aitana; Fierro, José Luís G.; De Lacey, Antonio L.; Ferrer, M. Luisa; Gutiérrez, María C. (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry